Rancang Bangun Sistem Pengawasan pada Ruangan Berbasis Internet of Things - Arifin Musthofa Wasis Waskito; Oczha Alifian Fernanda Rochim; Fadli Asmid; Eriyadi Nata Syahputra; Wahyu Pratama (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Internet of Things (IoT) is an era that connects devices and enables smarter and more connected interactions via the internet. In this era, CCTV is very necessary to monitor the condition of the room (house). This CCTV aims to monitor the room (house) when we as the owner are outside so that we feel safe. This time the researchers combined the implementation of CCTV and IoT using a localhost website with the aim that we as owners can access wherever we are without reducing the clarity of the resulting image quality. Researchers chose Web Localhost because Web Localhost uses the internet as its working system, and does not reduce the quality it obtains.